A study of transitions between technology push and demand pull strategies for accomplishing sustainable development in manufacturing industries. Issue 4 (18th April 2018) - Singla, Anuj; Sethi, APS; Ahuja, Inderpreet Singh
Abstract : Purpose: The purpose of this paper is to analyze transitions between technology push (TP) and demand pull (DP) strategies for accomplishing sustainable development in manufacturing industries. Design/methodology/approach: The key aspects based on their relevance to TP-DP strategies have been extracted from literature review. The aspects were utilized to design a well-framed TP-DP questionnaire. An extensive survey in medium- and large-scale manufacturing industries operating in India has been executed through questionnaire. The responses to various factors were collected and the data obtained have been analyzed using analytical and graphical comparisions. Findings: The recognition of the outcomes of transitions was perceived to be substantial. The research concludes that DP strategies dominates TP strategies in the present context. These strategies have emerged as a foundation for several development initiatives and actively support manufacturing industries in accomplishing sustainable development. Originality/value: The analysis shows that TP-DP strategies in Indian manufacturing industries encounter significant transitions at different stages of their development.